Customer Relationship Management and Patient Loyalty: The Mediating Role of Brand Salience and Customer Engagement Behavior - Dewi Kusuma Wijayanti; Endang Ruswanti; Johanes Johanes (International Forum of Researchers and Lecturers, 2026)
The increasing competition in the healthcare industry requires hospitals to establish effective relationship strategies to enhance patient loyalty. This study aims to examine the effect of Customer Relationship Management (CRM) on patient loyalty, with brand salience and customer engagement behavior (CEB) as mediating variables. The research adopts a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 155 outpatients at Cengkareng General Hospital (RSAR) who had experienced CRM-related services, using a structured questionnaire measured on a four-point Likert scale. The findings reveal that CRM has a significant positive effect on brand salience, customer engagement behavior, and patient loyalty. Among these relationships, CRM demonstrates the strongest influence on customer engagement behavior, indicating that relationship-based strategies effectively encourage active patient involvement. Furthermore, customer engagement behavior significantly affects patient loyalty, suggesting that patients who are more engaged—through feedback, recommendations, and participation—are more likely to develop stronger loyalty toward healthcare providers. In contrast, brand salience does not have a significant effect on patient loyalty, indicating that brand awareness alone is insufficient to drive loyalty in the healthcare context. Mediation analysis shows that customer engagement behavior partially mediates the relationship between CRM and patient loyalty, whereas brand salience does not act as a mediator. These results suggest that CRM enhances patient loyalty not only directly but also indirectly through strengthening engagement behavior. This study contributes to healthcare marketing literature by integrating relationship marketing and customer engagement perspectives, highlighting engagement as a more critical mechanism than brand salience in fostering sustainable patient loyalty.